The Epidemiological, Risk Factors and Clinical Characteristics of Ischemic Stroke in Ardabil Province, Iran: a Hospital Based Study - Ghasem Fattahzadeh-Ardalani; Afshan Sharghi; Abolfazl Atalu; Farzad Noori (Journal of Biostatistics and Epidemiology, 2020)
Introduction: Stroke is the third most common cause of death in world after heart diseases and cancer. Due to the higher rate of stroke and less attention to its occurrence, assessing the prevalence of ischemic brain stroke and its clinical patterns across countries and nations such as Iran could be valuable and important. Objectives: The aim of this study was to assess the epidemiological, Risk factor and clinical characteristics of ischemic stroke in Ardabil province. Materials and Methods: This descriptive cross-sectional study has been done on 676 patients with ischemic stroke who referred to Ardabil city hospital during at year 2018. Data collected by using a checklist including demographic and clinical data of patients. Collected data were analyzed by statistical methods in SPSS version 21. The p-value less than 0.05 was considered as significant. Results: Of all patients, 294 (43.5%) were female and rest of them were male. The mean age of patients was 69.3±13.2 years. Of all patients, 25.3% arrived to the hospital in less than 4.5 hours. The difference between arrival time to the hospital in rural and urban patients was significant. The most risk factors were seen in both sexes was HTN and in female only was DM and in male only was CVA. The results of CT and MRI showed that 30% and 64.9% of patients had lesion respectively that of them the most lesion in MRI was SMALL VESSEL and in CT was Middle Cerebral Artery (MCA). Conclusion: Results showed that the patients who live in urban areas arrive to emergency sooner than rural patients. The significant relation was seen between AF, residence place and valvular with arriving time to hospital.